The Oswego Canal: A Connecting Link Between The United States and Canada, 1819-1837 - Larkin, Janet (Ontario History, 2011)
In this article the author argues that the Oswego Canal (1825-1829) was a vital commercial link in the Great Lakes-Atlantic seaway, but its real worth became evident with the opening of Canada’s neighboring Welland Canal in 1829. The newly fashioned Oswego-Welland line offered an alternative route to the much publicized Erie Canal, and brought increased prosperity, settlement, and economic and social opportunities to the Great Lakes region. An important story in its own right, the Oswego Canal, especially in connection with Canada’s Welland, was one of North America’s more important systems of internal navigation.